Penguatan Kapasitas Guru UPT SDI Benteng Utara No. 59 Kepulauan Selayar Melalui Pelatihan Komunitas Belajar yang Efektif - Haris Haris; Muhammad Ansarullah S. Tabbu; Muh. Rais Abidin; Ramli Umar; Wahyu Hidayat M; Nurdin Nurdin; Indrayani Simpuruh (PT. Global Research Collaboration, 2024)
This program aims to improve the teaching capacity of teachers at UPT SDI Benteng Utara No. 59, Selayar Islands through training on developing effective learning communities. In the context of digital society 5.0, educational challenges continue to evolve, demanding innovative and relevant pedagogical approaches. Teachers in this school face issues of lack of collaboration, significant competency differences and inefficient management of learning community activities. The Community Service Program (PKM) was implemented to address these issues with a focus on increasing collaboration, reducing competency gaps, and improving activity management. The training involved preparation, implementation, and evaluation stages, using modules designed according to teachers' needs. The program results show an increase in collaboration between teachers, closure of competency gaps, efficiency of activity management, and learning quality. This shows that community service through a systematic approach to training can strengthen teaching capacity and improve education quality.